The Effects of Principal Leadership on Work Motivation and Performance of Teachers to Improve the Learning Outcomes on Science of the Fifth Grade Students of SD Tojo Una-Una Regency - Saiyan, Kamir Apoka; Rede, Amram; Abram , Paulus Hengky (Jurnal Riset Pendidikan MIPA, 2018)
The study aimed to determine whether there is an influence between the principal leadership on the learning outcomes on the science of the fifth-grade students of SD Tojo Una-Una Regency and to improve performance of teachers in improving learning outcomes on the science of the fifth-grade students of SD Tojo Una-Una Regency. This study used a type of quantitative research. The instruments in this study were a questionnaire sheet. The instrument test used Validity Test and Reliability Test. The data analysis technique used the t-test technique which is preceded by an analysis prerequisite test, namely the normality test and linearity test.Â P-value results of the normality test on the principal's leadership value (0.28)> 0.05 and student learning outcomes (0.17)> 0.05. thus, the data obtained were normally distributed. Therefore, the principal leadership can influence work motivation and performance of teachers, so that student learning outcomes also increase.